2017
DOI: 10.1155/2017/3820191
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis of Right Ventricle Involvement in Chagas Cardiomyopathy

Abstract: Right ventricle (RV) is considered a neglected chamber in cardiology and knowledge about its role in cardiac function was mostly focused on ventricular interdependence. However, progress on the understanding of myocardium diseases primarily involving the RV led to a better comprehension of its role in health and disease. In Chagas disease (CD), there is direct evidence from both basic and clinical research of profound structural RV abnormalities. However, clinical detection of these abnormalities is hindered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 80 publications
0
15
0
9
Order By: Relevance
“…In Chagas disease patients, dysfunction and dilation only of the LV have historically been studied; however, recent studies have demonstrated that RV dysfunction and dilation are predominantly seen in Chagas disease patients with heart failure [1,17]. Enlargement of the liver and other signs of systemic and pulmonary congestion are also commonly observed in severe CCM patients who die after the onset of heart failure [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Chagas disease patients, dysfunction and dilation only of the LV have historically been studied; however, recent studies have demonstrated that RV dysfunction and dilation are predominantly seen in Chagas disease patients with heart failure [1,17]. Enlargement of the liver and other signs of systemic and pulmonary congestion are also commonly observed in severe CCM patients who die after the onset of heart failure [18].…”
Section: Introductionmentioning
confidence: 99%
“…A disfunção diastólica pode ser considerada como um marcador precoce da doença, em populações de áreas não endêmicas e que os sinais de cardiomiopatia dilatada foram mais frequentes em pacientes com múltiplas anormalidades eletrocardiográficas. (PEREIRA JUNIOR et al, 2014;FERNANDEZ et al, 2015;SÁNCHEZ-MONTALVÁ et al, 2016;ROMANO et al, 2017).…”
Section: Apresentação E Discussão Dos Resultadosunclassified
“…Na forma com comprometimento leve a moderado do VE evidenciou uma redução global da função sistólica de todos os parâmetros. Além disso, pacientes com a forma indeterminada tiveram velocidades longitudinais mais baixas e os seguimentos inferiores foram os mais afetados, o que pode indicar o início de uma lesão miocárdica (BARBOSA et al, 2014;PEREIRA JUNIOR et al, 2014;LIMA et al, 2016;ROMANO et al, 2017;NUNES et al, 2018).…”
Section: Apresentação E Discussão Dos Resultadosunclassified
“…Conversely, an overall effect in favor of T. cruzi infection was identified for β -adrenergic density. There is no doubt that the heart is highly parasitized and damaged by T. cruzi [ 75 , 76 ]. Structural and electromechanical cardiac damage is the most serious manifestation of Chagas disease and is closely associated with morbidity and mortality, especially in the chronic phase of infection [ 77 79 ].…”
Section: Discussionmentioning
confidence: 99%